In the Supreme Court of the Northwest Territories, appeal from the Supreme Court of the Northwest Territories, Northern Alberta Judicial District [electronic resource] : Stobert et al. (defendants), appellants and Shorey et al. (plaintiffs), respondents : appeal book : Smith & West, advocates for appellants; Lougheed, McCarthy & Beck, advocates for respondents. - Stobart Sons & Co.; H. Shorey & Co.; Northwest Territories. Supreme Court. ([Calgary? : s.n., 1890)
Electronic reproduction. Mode of access: Internet. 44